PERKEMBANGAN FISIK DAN KOGNITIF PADA MASA KANAK-KANAK: Development, Childhood - Rohman, Ujang (Fakultas Pedagogi dan Psikologi Universitas PGRI Adi Buana Surabaya, 2010)
Childhood is a time-sensitive, where the child begins to sensitive receiving various efforts to develop all the potential that exists. Occur during maturation are sensitive functions of the physical and psychological ready to respond to stimuli that is given by the environment. Age period of 4-6 years is the development of the first basic physical abilities (motor), cognitive, language, sosia, l emotional, and cognitive. It is therefore necessary at this time and stimulation conditions appropriate to the needs of the child to the child's development will be achieved optimally. The process of development of physical abilities of children associated with the growth process child's motor, while the process of cognitive development related to the maturity of the way children think. Motor development of children consists of three main elements that are very dominant, namely: 1) The development of anatomical, these developments indicated a change in the quantity of bone structure, and height. 2) The development of physiological, these developments indicated a change of work on the organs. 3) The development of behavior, this development is the coordination between persyarafan and muscle functional and cognitive function, affective, and conative. Cognitive development occurs through a process he called adaptation. Adaptation is the adjustment to the demands of the environment through assimilation and accommodation.